Match-related activity profiles of youth female and male football players during World Cup classification tournaments and their relationship to body composition - Gómez-Villaseca, M.; Rehbein, C.; Earp, J.; Ramirez-Campillo, R.; Peñailillo, L. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: The activity profiles of football players during competition can be affected by the athletes` competitive level and sex. However, evidence of this in youth South American athletes is scarce as is the effects of body composition on match activity profiles. Therefore, the present study compared the activity profiles of Chilean under-20 (U20) and under-17 (U17) male and female teams during the World Cup qualification tournaments (WC) using a multicomponent athlete monitoring system and explored the relationships between these profiles and the players` body composition. METHODS: Athlete`s body composition was measured as there were total distance, distance covered at different velocities, explosive efforts, sprints, and estimated player load (PL) during the 2018-2019 World Cup Qualifiers. RESULTS: Males had greater muscle and lower fat mass than females and covered 10.8% more total distance with maximal speed being 15.3% faster in match play (P<0.05). However, females covered more distance at higher running speeds and had a greater number of sprints (P<0.05). For males, the U20 club was 3.7% faster and performed 26.3% more explosive efforts than the U17 club (P<0.05). Contrastingly, the female U17 club covered more total distance, more distance at different speeds had more total sprints, greater PL, and muscle mass than the U20 club (P<0.05). Across all athletes, fat mass correlated negatively to total distance (R=-0.39; P=0.001), while muscle mass correlated positively with maximal speed (R=0.72; P=0.001). CONCLUSIONS: Gender, competitive level, and body composition seem to affect match-activity profiles in football players during WC qualifiers.